2019
DOI: 10.1155/2019/5197983
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of In Vivo Aging in Human Bone Marrow Mesenchymal Stromal Cells Using Colony-Forming Unit-Fibroblast Assay and the CD45lowCD271+ Phenotype

Abstract: Uncultured mesenchymal stromal cells (MSCs) are increasingly used in therapies; however, the effects of donor age on their biological characteristics and gene expression remain unclear. The aim of this study was to investigate age-related changes in bone marrow (BM) MSCs following minimal or no culture manipulation. Iliac crest BM was aspirated from 67 healthy donors (19-89 years old) and directly used for the colony-forming unit-fibroblast (CFU-F) assay or CD45lowCD271+ cell enumeration. The colonies were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 74 publications
(122 reference statements)
8
76
0
Order By: Relevance
“…In minimally cultured BM-MSCs from differently aged donors, Ganguly et al [124] observed a reduction in number of CFUs (colony forming units), with increasing donor age, in accordance with others [90,121,125]; colony density was also reduced with age, indicating an age-related decline in number and proliferative capacity of MSCs. Conversely, minimal transcriptional and phenotypic changes were observed [124]. MSCs from foetal tissues are more plastic and grow faster than MSCs from adult bone marrow [126].…”
Section: In Vivo Msc Senescencesupporting
confidence: 65%
See 1 more Smart Citation
“…In minimally cultured BM-MSCs from differently aged donors, Ganguly et al [124] observed a reduction in number of CFUs (colony forming units), with increasing donor age, in accordance with others [90,121,125]; colony density was also reduced with age, indicating an age-related decline in number and proliferative capacity of MSCs. Conversely, minimal transcriptional and phenotypic changes were observed [124]. MSCs from foetal tissues are more plastic and grow faster than MSCs from adult bone marrow [126].…”
Section: In Vivo Msc Senescencesupporting
confidence: 65%
“…In general, aged MSCs display senescent features when compared with cells isolated from young donors, concomitant with reduced viability, proliferation and differentiation ability [121][122][123]. In minimally cultured BM-MSCs from differently aged donors, Ganguly et al [124] observed a reduction in number of CFUs (colony forming units), with increasing donor age, in accordance with others [90,121,125]; colony density was also reduced with age, indicating an age-related decline in number and proliferative capacity of MSCs. Conversely, minimal transcriptional and phenotypic changes were observed [124].…”
Section: In Vivo Msc Senescencementioning
confidence: 59%
“…To investigate the existence of phenotypically distinct BMSC subsets in OA trabecular bone, enzymatically extracted cells were processed for cell sorting and the BMSCs were gated based on the CD45-CD271+ phenotype while the CD45+CD271-hematopoietic-lineage cells (HLCs) were used as a negative non-BMSC control, as previously described [25][26][27] (Fig. 1a).…”
Section: Gene Expression Profile Of Cd271+ Bmsc Subsets In Oa Femoralmentioning
confidence: 99%
“…The fixed dishes were stained with methylene blue for CFU-F counting and were scanned for CFU-F area and integrated density (ID) analysis, as previously described (Ganguly et al, 2019;Sanjurjo-Rodriguez et al, 2019). Briefly, scanned images were converted to 8-bit format, calibrated, and analyzed using ImageJ software.…”
Section: Colony-forming Unit-fibroblast Assaymentioning
confidence: 99%